Diagnosed diabetes mellitus and in-hospital stroke mortality in a major sub-Saharan African urban medical unit. Issue 1 (February 2017) - Lekoubou, Alain; Clovis, Nkoke; Dzudie, Anastase; Kengne, Andre Pascal
Highlights: Currently, one out of five patients with acute stroke will die during the initial hospitalization. Traditional stroke risk factors are more frequent among diabetic patients. Having a history of known diabetes mellitus is not associated with a higher in-hospital death rate after a stroke. Abstract: Background: Estimates from developed countries show that early mortality after stroke is unaffected by diabetes status. Despite the high burden of both conditions in sub-Saharan Africa, data on the association between diabetes status and early mortality are lacking. Objective: In a major referral hospital in the Capital city of Cameroon, among acute stroke patients diagnosed using the World Health Organization criteria, we compared mortality rates in patents with and without known diabetes. Methods: Stroke patients with and without known diabetes were compared for demographic characteristics, risk factors, clinical, radiological, laboratory characteristic, and in-hospital mortality. Heterogeneities in mortality rates across major subgroups were investigated via interaction tests, and logistic regression accelerated failure-time models used to adjust for confounders . Results: Of the 1667 acute stroke patients included, 213 (12.8%) had diabetes mellitus. In general diabetic patients were older (median age 64.0 vs. 62.0 years, p  = 0.0006), and were more likely to have other stroke risk factors including a higher triglyceride levels on admission (106 vs. 97 mg/dL, p  = 0.044), a history of stroke (19.7% vs. 13.6%, p  = 0.022), and a history of hypertension (89.7% vs. 64.8%, p  < 0.0001). The death rates of diabetic patients and that of non-diabetic patients were similar (22.1% vs. 20.1%. p  = 0.524). This finding was similar across all pre-specified groups, with no evidence of interaction. Diabetes was unrelated with mortality in adjusted regression models. Conclusion: Diabetes is frequent among stroke patients in this setting, and often co-exists with other stroke risk factors. In-hospital mortality rate is equally high in diabetic and non-diabetic patients.